Patient safety culture among paramedic university students in Saudi Arabia - Hussin Albargi (PLoS ONE, 2026)
Background A strong and well-established patient safety culture is a fundamental component of healthcare systems and is especially vital in Emergency Medical Services (EMS). Understanding the attitudes of paramedic students toward patient safety offers valuable insights into their preparedness and highlights potential gaps in educational curricula requiring targeted enhancement. Objective This study aimed to evaluate the patient safety attitudes among paramedic university students in Saudi Arabia and explore differences based on demographic factors, including gender, academic year, and academic performance. Methods A cross-sectional survey was conducted with 494 paramedic students using the Safety Attitudes Questionnaire (SAQ), covering six domains: Teamwork Climate, Safety Climate, Job Satisfaction, Stress Recognition, Perception of Management, and Working Conditions. Statistical analyses included descriptive statistics, chi-square tests, ANOVA, and Bonferroni post-hoc comparisons. Results A total of 494 paramedic students participated. Overall, 25.1% achieved a positive safety attitude (SAQ ≥ 75). Among domains, Job Satisfaction scored highest (76.2 ± 15.2), while Stress Recognition scored lowest (51.2 ± 28.1). Significant differences were observed across academic years, with interns demonstrating higher domain scores than fourth-year students in teamwork climate, safety climate, stress recognition, job satisfaction, and perception of management (p < 0.01). Conclusion Paramedic students demonstrated low overall safety attitudes, with particularly low scores in stress recognition and reduced perceptions among fourth-year students. Strengthening stress management, teamwork, and supervisory support during training, alongside organisational efforts to enhance the clinical learning environment, may help improve the patient safety culture in paramedic education.